THE MICROBIAL "LANDSCAPE" OF THE DENTURE-BEARING AREA MUCOSA BEFORE AND AFTER THE PLACEMENT OF COMPLETE REMOVABLE DENTURES AND THE LOCAL IMMUNITY (Ustozlar uchun, 2026)
One of the main etiological factors affecting the oral ecosystem is the existence of teeth, whether whole or partial [1]. Specific habitats for microbial development and activity are found in dental fissures, carious cavities, root canals, gingival sulci, and dental plaque. The environmental circumstances for the oral microbiota undergo major modifications after partial or complete tooth loss and the subsequent installation of dental prosthesis [2]. The purpose of this study is to examine the oral microbiota of edentulous individuals both before to and six months after the implantation of full removable dentures.